2018
DOI: 10.21276/apalm.2191
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Renal Cell Carcinoma with Extensive Osseous MetaplasiaA Case Report

Abstract: Calcification is frequently seen histopathological and radiological finding in renal cell carcinoma (RCC). Occurrence of metaplastic bone is rare feature and majority are reported in clear cell renal cell carcinoma. We report a case of papillary renal cell carcinoma with extensive osseous metaplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the same review, only two cases of pRCC were found to have OM (4). Since then three new cases of pRCC with OM have been reported (2,5,6), making the total number of cases six, after the addition of the case of this report. Therefore, OM in pRCC is extremely rare.…”
Section: Discussionmentioning
confidence: 98%
“…In the same review, only two cases of pRCC were found to have OM (4). Since then three new cases of pRCC with OM have been reported (2,5,6), making the total number of cases six, after the addition of the case of this report. Therefore, OM in pRCC is extremely rare.…”
Section: Discussionmentioning
confidence: 98%